Continuing the Revolution : The Political Thought of Mao - Starr, John Bryan (Book collections on Project MUSE., 1979)
The author investigates the internal logic and evolution of Mao's theory in terms of various themes. Beginning with a consideration of conflict, which in Mao's view is a given and permanent component of society, Professor Starr then takes up the individual concepts of knowledge and action, authority, class and class conflict, organization, participation and representation, political education, political history, and political development. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print book.